1987
DOI: 10.3928/0090-4481-19870201-08
|View full text |Cite
|
Sign up to set email alerts
|

Language Disorders in Childhood and Adolescence: Implications for Learning and Socialization

Abstract: Children and adolescents with language disorders encounter disruption in the fluency of social interaction. Because of the chronic nature of language disabilities, problems in academic achievement and success become the hallmark of the disorders during the school years. Since adolescence represents a time of experimentation and definition of the self, individuals with language disorders are at high risk for the development of fragmented and inappropriate perspectives about themselves. Treatment must address, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Transitions associated with changes in curriculum as well as literacy demands may result in previously undisclosed difficulties with language tasks for certain children (Bashir, Wiig, & Abrams, 1988). A few studies have indicated that some children who score within normal limits on standardized language tests and who carry on acceptable casual conversations have difficulty learning to read (Liebergott, Menyuk, & Chesnick, 1988).…”
Section: Goals Of Assessmentmentioning
confidence: 98%
“…Transitions associated with changes in curriculum as well as literacy demands may result in previously undisclosed difficulties with language tasks for certain children (Bashir, Wiig, & Abrams, 1988). A few studies have indicated that some children who score within normal limits on standardized language tests and who carry on acceptable casual conversations have difficulty learning to read (Liebergott, Menyuk, & Chesnick, 1988).…”
Section: Goals Of Assessmentmentioning
confidence: 98%
“…Short-term follow-up evaluations over the preschool period have shown that many ELD children achieve normal levels of language proficiency by about age 5 to 6 years (Bishop & Edmundson, 1987;MacKeith & Rutter, 1972;Morley, 1972;Silva, 1980). The interpretation of this evidence for recovery from ELD is unclear, however, in light of strong evidence that longer-term outcomes may often be less favorable (ASHA, 1982;Bashir, Wiig, & Abrams, 1987;Wallach & Butler, 1984). That is, it has been shown that in later childhood and beyond, from 28% to 75% of children whose preschool language was impaired exhibit residual language/speech problems, and from 52% to 95% show impairments in reading achievement (Aram, Ekelman, & Nation, 1984;Aram & Nation, 1980;Fundudis, Kolvin, & Garside, 1979;Hall & Tomblin, 1978;Levi, Capozzi, Fabrizi, & Sechi, 1982;Padgett, 1988;Stark et al, 1984;Strominger & Bashir, 1977).…”
mentioning
confidence: 99%
“…Speech-language pathologists a r e becoming increasingly aware of the relationships among learning disabilities and mental health problems. It is now widely acknowledged that the anxieties, frustrations, and tension associated with learning disabilities and language and communication disorders may result in secondary emotional problems (Rashir, Wiig & Abrams, 1987;Lavoie, 1990). Preadolescents and adolescents with language and learning disabilities are often described as aggressive, defensive, direct, rude or stubborn, to mention but a few labels.…”
Section: Professional Perspectivesmentioning
confidence: 99%